Machinability investigations into special materials. Part 1 stainless steel Rex 448 hardened and tempered to Brinell minimum 321, maximum 375 - Purcell, J. (College of Aeronautics, 1954)
This Report deals with the machinability of Firth-Vickers materials. Reference REX WO (Stainless Steel) in the hardened and tempered condition* U,T.S 70-75 tons; Brinell hardness 321 minimum, 375 maximum. CONTENTS: SECTION 1 The development of a single point cutting tool (Lathe Tool). SECTION 2 The application of this tool to the turning process to determine the optimum surface speed and best feed rate. SECTION 3 The determination of the life of the cutting tool when used at optimum surface speed and best feed. SECTION 4 The modification of the single point tool to meet a special requirement; i.e. to be applied as a single tooth in a face milling cutter which is suitable for use when face milling Rex 1018 sheet in the hardened and tempered condition. The machining process must be designed to result in the minimum distortion in the finished component and give a good surface finish. Further, it is desirable that the finished dimensions shall be achieved at one pass and an area of 32 square feet be covered between re-grinds of the milling cutter. SECTION 5 Conclusions. SECTION 6 Results of practical application. Report on results of the application of the proposed cutter design, etc.